Sexual maturation of the Mongolian gerbil (Meriones unguiculatus): a histological, hormonal and spermatic evaluation - Pinto-Fochi, Maria Etelvina [UNESP]; Negrin, Ana Carolina [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Goes, Rejane Maira [UNESP] (CSIRO Publishing, 2014)
This study determined the phases of sexual development of the male Mongolian gerbil (Meriones unguiculatus) based on an integrative analysis of testicular morphology, hormonal data and sperm parameters. Male gerbils were analysed at 1, 7, 14, 21, 28, 35, 42, 50, 60, 70, 90, 100 and 120 days of age. Body, testicular and epididymal weights increased up to Day 70, 60 and 90, respectively. The impuberal phase, characterised by the presence of gonocytes, extended until Day 14. The prepubertal period lasted until Day 42, when puberty was achieved and a drastic increase in serum testosterone levels, mature adult Leydig cells and elongated spermatids was observed. Gerbils at 60 days of age showed a remarkable number of spermatozoa in the testis, epididymidis caput/corpus and cauda, and at Day 70 the maximum daily sperm production was reached. However, the gerbil may be considered sexually mature only from Day 90 onward, when sperm reserves become stable. The total transit time of spermatozoa along the epididymis of sexually mature gerbils was 11 days, with 1 day in the caput/corpus and 10 days in the cauda. These data cover a lacuna regarding the reproductive parameters of this rodent and provide foundations for its use in testicular toxicology studies.
Keywords: daily sperm production; epididymal sperm transit time; puberty; sperm motility